Studies on Triassic Fishes from East Greenland III. On Helmolepis gracilis Stensiö. - Nybelin, Orvar (Meddelelser om Grønland, 1977)
Three new specimens, preliminarily identified as Helmolepis gracilis STENSIÖ, are described and the identification is verified. The new material proves that Helmolepis a perleidid. The genus is not identical with any other perleidid genus described before 1932 and the name If Helmolepis is thus valid.